Grain Yield Losses in Wheat by Russian Wheat Aphid Diuraphis noxia (Mordvilko): Wheat Yield Losses by D. noxia (Biological Sciences - PJSIR, 2010)
Eight wheat cultivars were sown at the Regional Agricultural Research Institute, Bahawalpur, Pakistan, to evaluate their response to Russian wheat aphid (RWA) Diuraphis noxia (Mordvilko). Significant variability was observed among cultivars with respect to aphid infestation and yield losses. Cultivar V-2707 was the least infested with the aphid (6.3 aphids/tiller) giving maximum grain yield (4638 kg/ha), with cultivar V-2047 the second best with 6.43 aphids/ tiller infestation and grain yield of 4206 kg/ha. Commercial cultivars (Inqlab-91 and Punjab-96) were heavily infested with 14.4 and 12.6 aphids/tiller, respectively, and yielded 2245 and 2490 kg/ha harvest, respectively. Aphid population increased upto the fourth week of March and then declined. Aphid infestation resulted in 3.96 to 7.36% yield loss. The cultivar V-2707 was later released for general cultivation, under the name of Punjab-1.